MODAL PSIKOLOGIS DAN INTENSI JOB HOPPING PADA PEKERJA GENERASI MILLENIAL - Suryaratr, Ratna Dyah; Abadi, Muhammad Adib (Universitas Persada Indonesia YAI, 2018)
This study aims to find a relationship between psychological capital and job hopping intention in millenialworkers. Participants in the study are workers from millenial generation aged 18-28 that is currently workingfor less than 1 year in their current workplace. A quantitative method is used with questionnaire as instrument.Measurement is done using Job Hopping Intention Scale from Yuen (2016) and Psychological CapitalQuestionnaire-24 (PCQ-24) from Luthans, Youssef, and Avolio (2007) that were adapted to suit characteristicsof respondents. Result shows that there is a significant correlation between psychological capital and jobhopping intention among millenial workers. Psychological capital has a negative correlation with job hoppingintention with pearson correlation = -0.197 at 5% statistical significance. The study concludes that lower jobhopping intention was found among workers with higher psychological capital, and vice versa.